Determination of the Optimal In-Feed Amino Acid Ratio for Japanese Quail Breeders Based on Utilization Efficiency - Carvalho, Lizia C. [UNESP]; Mani, Tatyany S. A. [UNESP]; Lima, Michele B. [UNESP]; Pavanini, Jaqueline A. [UNESP]; Vieira, Rita B. [UNESP]; Amoroso, Lizandra [UNESP]; Silva, Edney P. [UNESP] (MDPI, 2022)
The description of the genetic potential is the first step to estimating amino acid requirements and the ideal amino acid relation (IAAR). The aim of this study was to estimate the parameters that describe the daily maximum theoretical nitrogen retention (NRmaxT, mg/BWkg0.67), daily nitrogen maintenance requirement (NMR, mg/BWkg0.67), protein quality (b), dietary efficiency of the limiting amino acid (bc−1) and determine the lysine requirement and the IAAR for Japanese quail breeders. Two nitrogen balance assays were performed, one assay using 49 quails distributed in seven treatments (protein levels between 70.1 and 350.3 g/kg) and seven replicates and other assay to determine the IAAR by the use of bc−1, 12 treatments and 10 replicate, with a control diet (CD) and 11 treatments that had limited essential amino acids by providing only 60% of the CD. The values obtained for NRmaxT, NMR, b and bc−1 were 3386.61, 0.000486 and 0.000101, respectively. The daily intake of Lys was 291 mg/bird day. Lys was set at 100% for determining the IAAR: 87, 67, 21, 117, 96, 66, 142, 39, and 133 for Met + Cys, Thr, Trp, Arg, Val, Ile, Leu, His, and Phr + Tyr, respectively, for Japanese quail breeders.
Keywords: dilution technique; exponential model; Goettingen approach; lysine requirement